Web-based learning management system focusing on assessment framework - Tan, Jia Wei (Nanyang Technological University, 2021)
Although the E-Learning market has been growing actively, usage of online learning platforms is minimal as the general intention is to complement physical learning. Hence, when the COVID-19 pandemic strikes unexpectedly, it resulted in online learning becoming a necessity and higher education institutions are frantically rushing to migrate all classes from in-person to remote learning. This also meant that lecturers are faced with the challenge to establish new routines and teach the course through online platforms which they are still trying to master. Learning management system tend to offer too many options which over complicate the content creation process. Lecturers are faced with difficulty with the creation process for quiz as there are too many configuration options given to the user when drafting content and assessment. Many of these features may be overlapping in functions and some are unintuitive. These features may be a result of the LMS vendor having to meet multiple use cases of different customers. This project aims to enhance the lecturers efficiency by creating a customised internal management system which cater to the needs for the school. By limiting it to just the key features, this allows simplicity in the user interface which will simplify the procedure in using the system. Students will be able to view their courses, attempt quizzes, review their grades and provide feedback. Whereas for lecturers, they are able to create different variety of quizzes, create different question sets, perform grading and lastly view the statistics. Ultimately, this system shows that having a customised learning management system could greatly improve the user experience for the student and the lecturers. Besides, there are still potential for this project to grow by expanding other key features apart from quiz into it. This project can be built from ground up by various students to achieve a fully customized and functional system like NUS in-built learning management system (LumiNUS).